2005
DOI: 10.1074/jbc.m409983200
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-specific Induction of a Novel Nuclear Factor-κB Regulator, IκB-ζ, via Toll/Interleukin-1 Receptor Is Mediated by mRNA Stabilization

Abstract: We have recently identified an inducible nuclear factor-B (NF-B) regulator, IB-, which is induced by microbial ligands for Toll-like receptors such as lipopolysaccharide and the proinflammatory cytokine interleukin (IL)-1␤ but not by tumor necrosis factor (TNF)-␣. In the present study, we examined mechanisms for stimulus-specific induction of IB-. The analysis of the IB-promoter revealed an essential role for an NF-B binding sequence in transcriptional activation. The activation, however, did not account for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
135
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(148 citation statements)
references
References 54 publications
10
135
3
Order By: Relevance
“…This protein, designated IκB-ζ , is barely detectable in resting cells, but is induced not only by LPS, but also by other microbial components that stimulate TLRs such as peptidoglycan, bacterial lipopeptide and CpG DNA [17][18][19]. The induction is also observed upon stimulation with IL (interleukin)-1β, but not by another pro-inflammatory cytokine, TNF (tumour necrosis factor)-α [17,20]. The protein IκB-ζ was also identified by other groups as MAIL (molecule possessing ankyrin repeats induced by LPS) [21] or INAP (IL-1-inducible nuclear ankyrin repeat protein) [22].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…This protein, designated IκB-ζ , is barely detectable in resting cells, but is induced not only by LPS, but also by other microbial components that stimulate TLRs such as peptidoglycan, bacterial lipopeptide and CpG DNA [17][18][19]. The induction is also observed upon stimulation with IL (interleukin)-1β, but not by another pro-inflammatory cytokine, TNF (tumour necrosis factor)-α [17,20]. The protein IκB-ζ was also identified by other groups as MAIL (molecule possessing ankyrin repeats induced by LPS) [21] or INAP (IL-1-inducible nuclear ankyrin repeat protein) [22].…”
Section: Introductionmentioning
confidence: 80%
“…We designated the longer form IκB-ζ (L) and the shorter form IκB-ζ (S), which lacks the N-terminal 99 amino acids of IκB-ζ (L). Both forms of IκB-ζ are induced upon stimulation, and IκB-ζ (L) is the predominant form in macrophages stimulated by LPS [20]. In contrast with the typical cytosolic and constitutively expressed IκB proteins, IκB-ζ is localized in the nucleus, where it preferentially binds, via the C-terminal ankyrin repeats, to the NF-κB p50 subunit rather than to the p65 subunit [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the possible explanations are epigenetic alterations of the gene locus in HepG2 cells or mRNA instability. The induction of IkB-z, a close relative of BCL3, requires activation by NF-kB and stimulus-specific stabilization of its mRNA (Yamazaki et al, 2005). Assuming a similar mechanism for BCL3, both NF-kB and Stat3 can activate transcription, but only NF-kB additionally stabilizes BCL3 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, human IkBz expression is strongly induced by TNFa (Totzke et al, 2006). Stimulation with TLR ligands results in the production of three different alternative splicing variants of IkBz: L, S, and D. IkBz (L) is predominantly expressed in response to LPS stimulation (Kitamura et al, 2002;Yamazaki et al, 2005), while expression of IkBz (S) has been observed at the mRNA and protein levels in minor species . Although IkBz (D) mRNA has been detected in macrophages, the corresponding protein has not been found.…”
Section: Introductionmentioning
confidence: 99%